Determination of the halogenated skeleton constituents of the marine demosponge Ianthella basta - Ueberlein, Susanne; Machill, Susanne; Schupp, Peter J.; Brunner, Eike (Marine Drugs, 2017)
Demosponges of the order Verongida such as Ianthella basta exhibit skeletons containing spongin, a collagenous protein, and chitin. Moreover, Verongida sponges are well known to produce bioactive brominated tyrosine derivatives. We recently demonstrated that brominated compounds do not only occur in the cellular matrix but also in the skeletons of the marine sponges Aplysina cavernicola and I. basta. Further investigations revealed the amino acid composition of the skeletons of A. cavernicola including the presence of several halogenated amino acids. In the present work, we investigated the skeletal amino acid composition of the demosponge I. basta, which belongs to the Ianthellidae family, and compared it with that of A. cavernicola from the Aplysinidae family. Seventeen proteinogenic and five non-proteinogenic amino acids were detected in I. basta. Abundantly occurring amino acids like glycine and hydroxyproline show the similarity of I. basta and A. cavernicola and confirm the collagenous nature of their sponging fibers. We also detected nine halogenated tyrosines as an integral part of I. basta skeletons. Since both sponges contain a broad variety of halogenated amino acids, this seems to be characteristic for Verongida sponges. The observed differences of the amino acid composition confirm that spongin exhibits a certain degree of variability even among the members of the order Verongida.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Amino acid composition; Demosponges; GC-MS; Halogenated amino acids; Ianthella basta; Skeletons; Spongin